Screening the Drug:H+ Antiporter Family for a Role in Biofilm Formation in Candida glabrata - Santos, Rui; Cavalheiro, Mafalda; Costa, Catarina; Takahashi-Nakaguchi, Azusa; Okamoto, Michiyo; Chibana, Hiroji; Teixeira, Miguel C. (Frontiers in Cellular and Infection Microbiology, 2020)
Biofilm formation and drug resistance are two key pathogenesis traits exhibited by Candida glabrata as a human pathogen. Interestingly, specific pathways appear to be in the crossroad between the two phenomena, making them promising targets for drug development. In this study, the 10 multidrug resistance transporters of the Drug:H+ Antiporter family of C. glabrata were screened for a role in biofilm formation. Besides previously identified players in this process, namely CgTpo1_2 and CgQdr2, two others are shown to contribute to biofilm formation: CgDtr1 and CgTpo4. The deletion of each of these genes was found to lead to lower biofilm formation, in both SDB and RPMI media, while their expression was found to increase during biofilm development and to be controlled by the transcription factor CgTec1, a predicted key regulator of biofilm formation. Additionally, the deletion of CgDTR1, CgTPO4, or even CgQDR2 was found to increase plasma membrane potential and lead to decreased expression of adhesin encoding genes, particularly CgALS1 and CgEPA1, during biofilm formation. Although the exact role of these drug transporters in biofilm formation remains elusive, our current model suggests that their control over membrane potential by the transport of charged molecules, may affect the perception of nutrient availability, which in turn may delay the triggering of adhesion and biofilm formation.